Pepper Weevil, Anthonomus eugenii Cano (Insecta: Coleoptera: Curculionidae) - John L. Capinera (EDIS)
The pepper weevil, Anthonomus eugenii Cano, is the most important insect pest of pepper in the southern United States. This document is EENY-278, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2002.